Peri-implantation urinary hormone monitoring distinguishes between types of first-trimester spontaneous pregnancy loss - Foo,L; Johnson,S; Marriott,L; Bourne,T; Bennett,P; Lees,C (Paediatric and Perinatal Epidemiology, 2020)
BackgroundLutenising hormone (LH) and human chorionic gonadotropin (hCG) hormone are useful biochemical markers to indicate ovulation and embryonic implantation, respectively. We explored “pointofcare” LH and hCG testing using a digital hometesting device in a cohort trying to conceive.ObjectiveTo determine conception and spontaneous pregnancy loss rates, and to assess whether trends in LHhCG interval which are known to be associated with pregnancy viability could be identified with pointofcare testing.MethodsWe recruited healthy women aged 1844 planning a pregnancy. Participants used a home monitor to track LH and hCG levels for 12 menstrual cycles or until pregnancy was conceived. Pregnancy outcomes (viable, clinical miscarriage, or biochemical pregnancy loss) were recorded. Monitor data were analysed by a statistician blinded to pregnancy outcome.ResultsFrom 387 recruits, there were 290 pregnancies with known outcomes within study timeline. Adequate monitor data for analysis were available for 150 conceptive cycles. Overall spontaneous firsttrimester pregnancy loss rate was 30% with clinically recognised miscarriage rate of 17%. The difference to LHhCG interval median had wider spread for biochemical losses (0.58.5 days) compared with clinical miscarriage (05 days) and viable pregnancies (06 days). Fixed effect hCG profile change distinguished between pregnancy outcomes from as early as day2 posthCG rise from baseline.ConclusionThe risk of firsttrimester spontaneous pregnancy loss in our prospective cohort is comparable to studies utilising daily urinary hCG collection and laboratory assays. A wider LHhCG interval range is associated with biochemical pregnancy loss and may relate to late or early implantation. Although early hCG changes discriminate between pregnancies that will miscarry from viable pregnancies, this pointofcare testing model is not sufficiently developed to be predictive.